Nonmedically Indicated Induction in Morbidly Obese Women is Not Associated With an Increased Risk of Cesarean Delivery. Issue 3 (September 2018) - Kawakita, T.; Iqbal, S.N.; Huang, C.C.; Reddy, U.M.
Abstract : ( Am J Obstet Gynecol. 2017;217:451.e1–e8) Morbid obesity is associated with an increased risk of cesarean delivery and maternal comorbidities compared with normal-weight women, hence the high prevalence of class II and class III obesity in women is concerning. Obesity is also a risk factor for stillbirth, especially at >39 weeks gestation. Data regarding the rate of cesarean delivery associated with nonmedically indicated induction of labor compared with expectant management in morbidly obese women are very limited. This retrospective cohort study aimed to evaluate the rate of cesarean delivery associated with nonmedically indicated induction of labor compared with expectant management in morbidly obese women without other comorbidities at term. Secondary outcomes were severe maternal and neonatal outcomes.